Validity and Reliability of Research Instrument in Evaluation of Work-Based Learning (WBL) Elements - Raden Ismail, Raden Mohd Farhan Helmy; Rahim, Mohd Bekri; Sulaiman, Junita (Online Journal for TVET Practitioners, 2023)
This study focuses on the evaluation of Work-Based Learning (WBL) elements on MTUN (assumed to be a specific institution or program) bachelor students. The objective is to assess the validity and reliability of the research instruments used in the evaluation process. WBL is an educational approach that integrates practical work experiences with academic learning to enhance students' skills and employability. Ensuring the validity of the research instruments is crucial to measure the intended outcomes accurately. Content validity is achieved through careful instrument design, aligning research questions with measures, and seeking expert input. Reliability is established by employing standardized procedures, clear instructions, and rigorous data collection training. This study utilizes a mixed-methods approach, combining quantitative surveys and qualitative interviews, to enhance the validity and reliability of the findings. Limitations and potential sources of bias are acknowledged and addressed. By maintaining validity and reliability in the evaluation, this study aims to provide accurate and trustworthy insights into the effectiveness of WBL elements, contributing to the improvement of WBL programs and enhancing student learning outcomes and career readiness.